Evaluation of the blended public health empowerment program-basic field epidemiology in the Eastern Mediterranean Region - Alsouri, Ruba Kamal; Khader, Yousef; Bashier, Haitham; Amiri, Mirwais; Morsy, Sara Abdelkarim; Abbas, Zainab Naseer; Farah, Zeina Elias; Al Nsour, Mohannad (Frontiers in Medicine, 2024)
Introduction The COVID-19 pandemic encouraged the shift toward technology-based learning globally, impacting education systems profoundly. In response to this emerging need, the Eastern Mediterranean Public Health Network (EMPHNET) adapted its Public Health Empowerment Program-Basic Field Epidemiology (PHEP-BFE) to a Blended Learning Model. This study evaluates the Blended PHEP-BFE program in Iraq, Egypt, and Lebanon, focusing on participant reactions and learning outcomes. Methods A descriptive evaluation was conducted, aligned with the first two levels of Kirkpatrick's model. Online questionnaires were administered to participants and facilitators through EMPHNET's Learning Management System (LMS). Qualitative and quantitative data were analyzed to assess program effectiveness, satisfaction, and challenges. Results A total of 138 PHEP-BFE participants (119 (86.2%) males and 19 (13.8%) females) from Iraq (n = 61), Egypt (n = 66), and Lebanon (n = 11) responded to the questionnaire. The majority of the participants (96.4%) reported that they were satisfied with PHEP-BFE. Notably, 77.5% of participants rated the blended learning program as very good or excellent, 18.1% rated it good, and 3.6% found it average, with a minimal 0.7% expressing dissatisfaction. The majority of participants agreed that the blended PHEP-BFE enhanced their capacity to conduct, review and monitor surveillance data (95.7%), perform descriptive data analysis (94.2%), effectively communicate information with agency staff and the local community (95.7%), write summaries of surveillance findings or outbreak investigations (95.7%), use MS Excel to enter, analyze, and display public health surveillance data (91.3%), prepare and administer an oral presentation for fieldwork (94.9%), and increase their knowledge of fundamental field epidemiology (94.9%). The participants responded positively to the program's content, training duration, learning platform, facilitators and mentors, and fieldwork. Conclusion The study showcases the success of the blended PHEP-BFE in diverse contexts, emphasizing positive participant reactions and improved competencies. The evaluation underscores the program's success in advancing public health training in the EMR. Blended learning models prove promising for future FETP initiatives, contributing valuable insights to public health workforce development. Positive outcomes and identified challenges, provide a roadmap for continuous improvement.